Pelatihan Dasar-Dasar Komputer Sebagai Persiapan Menyambut Pelaksanaan Asesmen Nasional Berbasis Komputer Pada Siswa SD Negeri 218 Congkoe - Nur Farolai; Nurjannah Nurjannah (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
This basic computer basic training aims to facilitate students in preparing themselves to welcome the implementation of the Computer-Based National Assessment (ANBK). There are several obstacles from this research because students still do not understand about computers. This implementation method is carried out by direct practicum method and lecture method. The training participants were 12 grade 5 students. The training took place in the class room of SD Negeri 218 Congkoe. Based on the training carried out, the desired results are achieved well, namely students become more skilled in operating computers.